Pelatihan dan Pendampingan Pengelolaan BUMDes Berbasis Digital untuk Meningkatkan Kapasitas Manajerial di Desa Poter Kabupaten Bangkalan - Indien Winarwati; Ach. Mus’if; Moh Karim; Achmad Thoriqil Huda; Tri Pujiati (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
The difficulties in preparing accountable financial reports, planning business development strategies, and managing business operations effectively remain major challenges faced by the managers of the Village-Owned Enterprise (BUMDes) in Poter Village, Tanah Merah District, Bangkalan Regency. These limitations have hindered the optimal growth of several business units, with some experiencing stagnation and limited contribution to local economic development. The condition indicates that strengthening managerial and financial management capacities is essential to improve the performance and sustainability of BUMDes. This community service activity aims to enhance the capacity of BUMDes managers through a structured training program. The implementation methods include preliminary observation, training sessions, mentoring, and evaluation through interviews and documentation. The training materials focus on business management, basic accounting, and financial reporting preparation. This activity is also aligned with the Sustainable Development Goals initiated by the United Nations, particularly Goal 1 (No Poverty), Goal 8 (Decent Work and Economic Growth), and Goal 9 (Industry, Innovation, and Infrastructure). By strengthening managerial and financial capacities, this program contributes to improving income-generating activities, fostering local entrepreneurship, and supporting sustainable rural economic development. The results show an improvement in participants’ understanding and skills in business management, as well as increased awareness of the importance of proper administration and financial reporting. Participants also demonstrated positive responses to the program. Furthermore, the outcomes of this program indicate its contribution to achieving SDGs targets at the village level, especially in enhancing economic resilience and institutional capacity of community-based enterprises. Therefore, this training and mentoring activity is effective in strengthening the capacity of BUMDes managers and contributes to improving performance and sustainability of village enterprises. Similar programs should be conducted continuously to ensure optimal development of BUMDes and to enhance rural community welfare.